2018
DOI: 10.3390/ijms19113536
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Combination of Low VEGFR-1 and High VEGFR-2 Expression in Endothelial Cells of Colorectal Cancer

Abstract: Research on tumor angiogenesis has mainly focused on the vascular endothelial growth factor (VEGF) family and on methods to block its actions. However, reports on VEGF receptor (VEGFR) expression in tumor-associated endothelial cells (ECs) are limited. Thus, we evaluated VEGF, VEGFR-1 and VEGFR-2 expression in ECs of colorectal cancer (CRC) using immunohistochemistry. VEGF, VEGFR-1 and -2 expression in ECs was quantitatively evaluated by digital image analysis in a retrospective series of 204 tumor tissue samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…There was no significant association of the expression levels of VEGFR 1-3 and overall survival. Nonetheless, these results are in line with previous studies on other gastrointestinal malignancies [ 35 , 36 ]. This might in part be explained by the fact that well- to moderately differentiated GEP-NENs have a favorable overall survival even in the presence of distant metastases and that there was no significant correlation between tumor grading and the expression of VEGFRs.…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant association of the expression levels of VEGFR 1-3 and overall survival. Nonetheless, these results are in line with previous studies on other gastrointestinal malignancies [ 35 , 36 ]. This might in part be explained by the fact that well- to moderately differentiated GEP-NENs have a favorable overall survival even in the presence of distant metastases and that there was no significant correlation between tumor grading and the expression of VEGFRs.…”
Section: Discussionsupporting
confidence: 93%
“…These effects are mediated by the phosphorylation of VEGFR on vascular endothelial cells. Indeed, VEGFR expression on cancer cells has been reported (28,30), which enables accelerating proliferation via autocrine growth factor signaling cascades. However, VEGFR expression was not detected in the ATC cell lines used in the present study, suggesting that the VEGF-VEGFR autocrine cascade may be limited in ATC.…”
Section: Discussionmentioning
confidence: 99%
“…They also emphasized the value of determining changes in their expression, while stressing that it would be reasonable to simultaneously assess the level of both receptors. This will allow to determine the relationship between receptors and increase the sensitivity and precision of the assay [ 45 ]. In turn, Kopparapu et al observed a higher level of VEGF-A , VEGFR-1 , VEGFR-2 in all bladder cancer samples compared to the control.…”
Section: Discussionmentioning
confidence: 99%